New technologies and branding - Sachetti, Philippe, 1958-; Zuppinger, Thibaud (Innovation, entrepreneurship, management series. Innovation and technology set, 2018)
Between cases of study, theoretical panorama and practical reflections, this book gives brand leaders the means to defend their brand in a changing environment, where new technologies and manipulation techniques have rendered old defense schemes obsolete. Rather than suggesting a reflection from the point of view of the crisis, the authors deal with the question under another, broader theme: conflict.